Dialogamos sobre situaciones que nos ponen en peligro - Montero Rodriguez, Vannesa (2019)
The present work is focused especially on students getting to know and talk about situations where there is a danger of violation of their personal space and learn to take care of those that represent a danger to their safety._x000D_ In this way, giving to know that the work promotes in our students the care opposite to a danger situation in the family, school and community, as teachers we want to train students capable of facing different risk situations that threaten against their life or that of your neighbor, solve their problems and to go to the people to ask for help._x000D_ We held the session entitled: We talk on situations that put us in danger, it was developed in the area of Social Personnel and for students of the second grade, taking into account the competence to Build your identity, in which the ability of the student to Identify the people who show them affection and who make them feel protected and safe, it uses them when you need them and acts responsibly in the face of different situations of danger._x000D_ In the preparation of the learning session, the pedagogical processes of a session and didactics of the area have been taken into account in order to promote the active and meaningful participation of students during the development of the same making use as instrument a checklist to verify the purpose of the new learning